Cheltuielile și consumul - Tatu, Mădălina (Calitatea Vieții, 1994)
The study contains the analysis of the consumption (through the declared spendings of the interviewed households) and the influence of the self-consumption on the structure of the spendings (through the modification of the percentages for some spendings). The influence of the residential environment (urban/rural), the different social categories (peasants, employment, unemployment) have been equally studied. As for the evaluation of the minimum living standard (decent, adapted, of subsistence) in August 1993, some family types have been studied, determining their influence on these family types.